Magnesium Phthalocyanines and Tetrapyrazinoporphyrazines: The Influence of a Solvent and a Delivery System on a Dissociation of Central Metal in Acidic Media - Kolarova, Michaela; Mulaku, Anita; Miletin, Miroslav; Novakova, Veronika; Zimcik, Petr (Pharmaceuticals, 2022)
Magnesium complexes of phthalocyanines (Pcs) and their aza-analogues have a great potential in medical applications or fluorescence detection. They are known to demetallate to metal-free ligands in acidic environments, however, detailed investigation of this process and its possible prevention is lacking. In this work, a conversion of lipophilic and water-soluble magnesium complexes of Pcs and tetrapyrazinoporphyrazines (TPyzPzs) to metal-free ligands was studied in relation to the acidity of the environment (organic solvent, water) including the investigation of the role of delivery systems (microemulsion or liposomes) in improvement in their acido-stability. The mechanism of the demetallation in organic solvents was based on an acidoprotolytic mechanism with the protonation of the azomethine nitrogen as the first step and a subsequent conversion to non-protonated metal-free ligands. In water, the mechanism seemed to be solvoprotolytic without any protonated intermediate. The water-soluble magnesium complexes were stable in a buffer with a physiological pH 7.4 while a time-dependent demetallation was observed in acidic pH. The demetallation was immediate at pH < 2 while the full conversion to metal-free ligand was done within 10 min and 45 min for TPyzPzs at pH 3 and pH 4, respectively. Incorporation of lipophilic magnesium complexes into microemulsion or liposomes substantially decreased the rate of the demetallation with the latter delivery system being much more efficient in the protection from the acidic environment. A comparison of two different macrocyclic cores revealed significantly higher kinetic inertness of magnesium TPyzPz complexes than their Pc analogues.